Status update on bioelectrochemical systems: Prospects for carbon electrode design and scale-up - Herkendell, Katharina (Catalysts, 2021)
Bioelectrochemical systems (BES) employ enzymes, subcellular structures or whole electroactive microorganisms as biocatalysts for energy conversion purposes, such as the electrosynthe-sis of value-added chemicals and power generation in biofuel cells. From a bioelectrode engineering viewpoint, customizable nanostructured carbonaceous matrices have recently received considerable scientific attention as promising electrode supports due to their unique properties attractive to bioelectronics devices. This review demonstrates the latest advances in the application of nano- and micro-structured carbon electrode assemblies in BES. Specifically, in view of the gradual increase in the commercial applicability of these systems, we aim to address the stability and scalability of different BES designs and to highlight their potential roles in a circular bioeconomy.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bioeconomy; Bioelectrocatalysis; Bioelectrode; Bioenergy; Biofuel cells; Electrosynthesis; Enzyme; Mesoporous carbon; Microorganisms; Nanostructures; Waste valorization